Raised bed in a private garden in Yellowknife, NWT ... - Campbell, Sandy (University of Alberta Library, 2015)
Raised beds are common in Yellowknife, where there is little topsoil in which to make a garden. In this bed there are several flowers, herbs and vegetables including: marigolds, pansies, parsley, and chives (in bloom). ...